Aliens in the attic [videorecording (DVD)] - Schultz, John; Richter, Andy, 1966-; Meadows, Tim, 1961-; Tisdale, Ashley, 1985-; Nealon, Kevin, 1953- (20th Century Fox Home Entertainment, 2009)
"It's summer vacation, but the Pearson family kids are stuck at a boring lake house with their nerdy parents. That is until feisty, little, green aliens crash-land on the roof, with plans to conquer the house and Earth! Using only their wits, courage and video game-playing skills, the youngsters must band together to defeat the aliens and save the world, but the toughest part might be keeping the whole thing a secret from their parents!"--Container.